Awareness of and the relationship between noise-induced hearing loss and the use of personal listening devices in Jazan region, Saudi Arabia - Mokhatrish, Mohammad M.; Dighriri, Ramzi M.; Otaif, Abdulrahman A.; Otaif, Abdulelah A.; Jahlan, Riyadh A.; Daghreeri, Abdulrahman A.; Hakami, Hussam T.; Mobarki, Ameer M.; Daghriri, Bandar F.; Hakami, Fawaz M.; Dighriri, Osama M. (Frontiers in Public Health, 2025)
ObjectivesNoise-induced hearing loss (NIHL) is a significant global health issue, exacerbated by the increasing use of personal listening devices (PLDs). This study aims to assess the awareness of NIHL and its association with PLD use among residents in the Jazan region of Saudi Arabia.Materials and methodsA descriptive, cross-sectional study was conducted among Saudi adults in Jazan. A structured questionnaire was used to gather data on demographics, health-related characteristics, PLD usage patterns, and awareness of NIHL.ResultsThe study included 428 participants, with 53.3% males and 45.6% aged 18–25. Most participants used PLDs frequently, with 43.0% listening for an hour or less daily. Awareness of NIHL was moderate, with 81.1% recognizing the harmful effects of loud noise on hearing. However, misconceptions about early signs and prevention of hearing loss (HL) were prevalent. The mean HL score was 8.9 (SD: 2.8) out of 20; which reflects low level of HL among the study participants. Males were 1.6 folds more likely to have higher level of HL compared to females (p = 0.015). Participants who prefer high volume level (above 70 dB) were more than 2-folds likely to have higher level of HL compared to others (p < 0.01).ConclusionThe study highlights moderate level of awareness of NIHL and the risks of PLDs in Jazan region of Saudi Arabia. However, implementing preventive measures, especially among younger demographics, remains a challenge. The findings suggest the need for targeted public health interventions and technology to strengthen hearing conservation strategies.